Dancing with the Devil: A Study of Country Size and the Incentive to Tolerate Money Laundering - H. Gnutzmann; K. Mccarthy; Brigitte Unger (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2008)
The incidence of money laundering, and the zeal with which international anti-money laundering (AML) policy is pursued, varies significantly from country to country, region to region. There are, however, quite substantial social costs associated with a policy of toleration, and this begs the question as to why such variance should exist. In this paper we claim that, due to the globalisation of crime, if a single country should break the "chain of accountability'', then it will provide a safe haven for criminals and attract the total financial proceeds of crime. Because smaller economies are best able to insulate themselves from the costs of crime, smaller countries therefore bear only a tiny share of the total costs relative to potential benefits of investment that money laundering offers, and so have a higher incentive to tolerate the practice compared to their larger neighbours. As such, we claim that the existence of a money laundering market is due to a policy of AML 'defection', and that the degree of 'defection' depends largely on the physical size of the country. In this paper we present a simple model of policy competition which formalises this intuition.
Keywords: 330; Money Laundering; Policy Competition; Systems Competition